Predictors of survival in patients with amyotrophic lateral sclerosis: A large meta-analysis - Wei-Ming Su (Elsevier, 2021)
Background: The survival time of amyotrophic lateral sclerosis (ALS) is greatly variable and protective or risk effects of the potential survival predictors are controversial. Thus, we aim to undertake a comprehensive meta-analysis of studies investigating non-genetic prognostic and survival factors in patients with ALS. Methods: A search of relevant literature from PubMed, Embase, Cochrane library and other citations from 1st January 1966 to 1st December 020 was conducted. Random-effects models were conducted to pool the multivariable or adjusted hazard ratios (HR) by Stata MP 16.0. PROSPERO registration number: CRD42021256923. Findings: A total of 5717 reports were identified, with 115 studies meeting pre-designed inclusion criteria involving 55,169 ALS patients. Five dimensions, including demographic, environmental or lifestyle, clinical manifestations, biochemical index, therapeutic factors or comorbidities were investigated. Twenty-five prediction factors, including twenty non-intervenable and five intervenable factors, were associated with ALS survival. Among them, NFL (HR:3.70, 6.80, in serum and CSF, respectively), FTD (HR:2.98), ALSFRS-R change (HR:2.37), respiratory subtype (HR:2.20), executive dysfunction (HR:2.10) and age of onset (HR:1.03) were superior predictors for poor prognosis, but pLMN or pUMN (HR:0.32), baseline ALSFRS-R score (HR:0.95), duration (HR:0.96), diagnostic delay (HR:0.97) were superior predictors for a good prognosis. Our results did not support the involvement of gender, education level, diabetes, hypertension, NIV, gastrostomy, and statins in ALS survival. Interpretation: Our study provided a comprehensive and quantitative index for assessing the prognosis for ALS patients, and the identified non-intervenable or intervenable factors will facilitate the development of treatment strategies for ALS. Funding: This study was supported by the National Natural Science Fund of China (Grant No. 81971188), the 1.3.5 project for disciplines of excellence, West China Hospital, Sichuan University (Grant No. 2019HXFH046), and the Science and Technology Bureau Fund of Sichuan Province (No. 2019YFS0216).